SELF-EFFICACY MATEMATIS MAHASISWA PENDIDIKAN MATEMATIKA DITINJAU DARI PERBEDAAN GENDER - Rohantizani Rohantizani (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2018)
This study aims to examine students' mathematical self-efficacy reviewed under gender. This research uses descriptive design. Data obtained from the spread of scale of self-efficacy to students of mathematics education courses at Malikussaleh University as many as 38 people, 8 men and 30 women. The scale of self-efficacy online is spread on April 2018 in a two-week period. Data were analyzed by descriptive analysis technique using normal curve approach. The results showed that the mean of male mathematical self-efficacy was 64 and the mean of female mathematical self-efficacy was 59,83. Mathematical self-efficacy of male and female students is in the medium and high category.